Could the YEARS algorithm be used to exclude pulmonary embolism during pregnancy? Data from the CT‐PE‐pregnancy study - Langlois, Emilie; Cusson‐Dufour, Camille; Moumneh, Thomas; Elias, Antoine; Meyer, Guy; Lacut, Karine; Schmidt, Jeannot; Le Gall, Catherine; Chauleur, Céline; Glauser, Frédéric; Robert‐Ebadi, Helia; Righini, Marc; et al. (Journal of thrombosis and haemostasis, 2019)
Introduction The recently proposed YEARS algorithm was shown to safely exclude pulmonary embolism (PE) and reduce the use of computed tomography pulmonary angiography (CTPA) among pregnant women with suspected PE. Our aim was to externally validate this finding. Methods We performed a post hoc analysis of a prospective management outcome study for PE diagnosis in pregnant women. PE was diagnosed with an algorithm that combined the revised Geneva score, D‐dimer testing, bilateral lower‐limb compression ultrasonography, and CTPA. All women had a 3‐month follow‐up. All of the items necessary to use the YEARS algorithm were prospectively collected at the time of the study. Results Of the 395 women included in the original study, 371 were available for the present analysis. The PE prevalence was 6.5%. Ninety‐one women had no YEARS items, and 280 had one or more items. When the YEARS items were combined with D‐dimer levels (<1000 ng/mL in women with no items, and <500 ng/mL in women with one or more items), 77 women (21%) met the criteria for PE exclusion and would not have undergone CTPA as per the YEARS algorithm. None of these 77 women had PE diagnosed during the initial work‐up or 3‐month follow‐up. Therefore, the failure rate of the YEARS algorithm in our pregnant women population was 0/77 (95% confidence interval 0.0‐3.9). Conclusion In our study, application of the YEARS algorithm would have resulted in safe exclusion of PE in one of five pregnant women without the need for radiation exposure, further supporting the use of the algorithm in this population.